The first estate as the fourth content analysis of the coverage by the CBCP news and UCA news of the 2022 Philippine presidential elections - Corpuz, Jomarc Angelo Marcos 2001
This study analyzes the coverage of the Catholic Bishops' Conference of the Philippines News (CBCP News) and the Union of Catholic News during the 2022 Philippine Presidential Elections. Eighty-two election-related articles published from February 8, 2022, to May 8, 2022, from the two Catholic news outlets, were content-analyzed under the light of the Framing Theory. The research found that CBCP News and UCA News showed preferences in their reporting and covered with the interest of the Catholic Church and its audience in its mind. The content analysis also showed that, despite not being stated outright, the two Catholic media pushed a narrative supporting, former Vice President Leni Robredo and abasing President Ferdinand Marcos Jr. This portrayal, along with the sheer number of times the two were mentioned, may have swayed some voters in the past polls.